A quality project : prevalence – interventions : prevalence of pressure ulcers, eating difficulties and hospital hygiene - Ólína Torfadóttir 1942- (2011)
Verkefnið er lokað til 1. janúar 2013 The subject of this paper can be categorised as a quality project, the aim of which was to improve quality of nursing and increase patient safety in three major fields of nursing; pressure ulcers, nutrition and hospital hygiene. The paper is based on collaboration between Akureyri Hospital and a research group at Kristianstad University College, Sweden. The data analysed consist of the results from six quality evaluations, which were carried out on the basis of previous evaluations which called for improvements. Improvements were implemented through an action plan for a set period of time and then the evaluations were repeated. A comparison was made with results from previous evaluations. The results will form the basis for further development. The method used consists of frequency measurements (point prevalence studies) on a predetermined day, followed by an agreed intervention, and repeated prevalence measurement approximately one year later (P-I-P method). The rise in prevalence of pressure ulcers between 2005 (n= 34) and 2007 (n=48) is attributable to the increase in proportion of grade 1 pressure ulcers. Total 98 (2005) patients and 110 (2007) patients were included. Pressure ulcers of grade 1 were 88% (n=30) in 2005 and 96% (n= 46) in 2007. Pressure ulcers of grade 3 or 4 were recorded neither in 2005 nor in 2007. Sacral pressure ulcers decreased from 18% (n=6) 2005 to 6% (n=3) in 2007. The routine use of Modified Norton Scale increased significantly (p < 0.000) from 2005 (0%) to 46% 2007 (n=51). There was a significant improvement in risk assessment and use of turning/moving schedules (p < 0.003). The results of the malnutrition/eating difficulties study showed a significant increase (p < 0.001) in documenting BMI in the charts, from one patient in 2006 to 28 patients in 2007. In 2006, 85 patients took part and 92 patients in 2007. In total 63% (n= 60) of the patients in 2006 and 58% (n=53) in 2007 had various eating difficulties. Unintentional weight loss ...